Performance of Single Pass Earth-Tube Heat Exchanger: An Experimental Study - Sharan, Girija; Jadhav, Ratan (Journal of Agricultural Engineering, 2003)
A single pass earth-tube heat exchanger (ETHE) was installed to study its performance in cooling and heating modes. ETHE consisted of 50 m mild steel pipe of 10 cm nominal diameter and 3 mm wall thickness, buried 2.85 m deep below ground. Ambient air was pumped through it for conditioning. Tests were conducted on three consecutive days in each month. The ETHE conditioned 5.6 mÂ³/min of 40.6degree C air to 26.6degree C in cooling mode, and 8.3degree C air to 23.0degree C in heating mode. Average COP was 3.3 in cooling and 3.8 in heating mode.